2021
DOI: 10.1177/10760296211053313
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Plasma Exchange Protects Patients with Sepsis-Associated Disseminated Intravascular Coagulation by Improving Endothelial Function

Abstract: The mortality rate of sepsis-associated disseminated intravascular coagulation (DIC) is high. This study aimed to explore the efficacy of therapeutic plasma exchange (TPE) in sepsis-associated DIC patients by improving endothelial function. A total of 112 sepsis-associated DIC patients were randomly divided into the TPE group (n = 40), the heparin (HP) group (n = 36), and the SHAM group (n = 36). The SHAM group received conventional treatment; the HP group was treated with HP based on conventional treatment; a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 23 publications
1
18
0
Order By: Relevance
“…TPE has also repeatedly been reported as a therapeutic option in sepsis-mediated disseminated intravascular coagulopathy (DIC). A recent prospective study found improved platelet counts, coagulation function and even increased survival rates after TPE [ 63 ] which is in line with observations in patients with organ failure, DIC, meningococcal septicemia, Capnocytophaga canimorsus infection and scorpion bites [ 63 66 ].…”
Section: Question 5 What Are Explorative Tpe Indications For Critical...supporting
confidence: 78%
“…TPE has also repeatedly been reported as a therapeutic option in sepsis-mediated disseminated intravascular coagulopathy (DIC). A recent prospective study found improved platelet counts, coagulation function and even increased survival rates after TPE [ 63 ] which is in line with observations in patients with organ failure, DIC, meningococcal septicemia, Capnocytophaga canimorsus infection and scorpion bites [ 63 66 ].…”
Section: Question 5 What Are Explorative Tpe Indications For Critical...supporting
confidence: 78%
“…Adults. There were 6 RCTs [25][26][27][28][29][30] and 2 observational studies 31,32 with a total of 632 adults with 280 in the TPE arm. The mean age of the adult patients was 49.95 years (95% CI: 48.02, 51.89).…”
Section: Demographicsmentioning
confidence: 99%
“…Six studies did not clearly note the time of TPE initiation but described as "institutionand physician-dependent." 25,27,28,31,32,36 For anticoagulation strategy, 5 studies used heparin, 26,27,35,37,38 4 adopted citrate 28,31,33,34 while 3 did not specify. 30,32,36 Adult studies.…”
Section: Tpe Regimementioning
confidence: 99%
“…Plasma exchange therapy in TMA is considered helpful in replenishing ADAMTS13, eliminating antibodies to ADAMTS13, replacing normal-sized von Willebrand factor (vWF), and eliminating ultra vWF multimers and excess cytokines. Plasma exchange therapy also had a role in sepsis or septic shock with DIC, TMA, and multiple organ dysfunction [50][51][52][53]. Plasma exchange therapy also benefited septic patients with decreased ADAMTS13 activity [54].…”
Section: Discussionmentioning
confidence: 99%